Mucoadhesive beads of gellan gum/pectin intended to controlled delivery of drugs - Prezotti, Fabiola Garavello [UNESP]; Cury, Beatriz Stringhetti Ferreira [UNESP]; Evangelista, Raul Cesar [UNESP] (Elsevier B.V., 2014)
Gellan gum/pectin beads were prepared by ionotropic gelation, using Al3+ as crosslinker. High yield (92.76%) and entrapment efficiency (52.22-88.78%) were reached. Beads exhibited high circularity (0.730-0.849) and size between 728.95 and 924.56 m. Particle size and circularity was increased by raising polymer and crosslinker concentrations. Polymers ratio did not influence beads properties. The materials stability and the absence of drug-polymers interactions were evidenced by thermal analysis and FM The high beads mucoadhesiveness was evidenced by in vitro and ex vivo tests. The erosion of beads was greater in acid media while swelling was more pronounced in pH 7.4. Drug release was dependent on pH in which samples 11H1-3, 11H1-5 and 41H1-3 released only 34%, 20% and 22% of ketoprofen in pH 1.2, while in pH 7.4 the drug release was sustained up to 360 min. Korsmeyer-Peppas model demonstrated that drug release occurred according to super case-II transport. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Beads; Gellan gum; Pectin; Ionotropic gelation; Controlled release; Ketoprofen